Peran Dewan Pengawas Syariah Dalam Perbankan Syariah - Rahmat Ilyas (JPS (Jurnal Perbankan Syariah), 2021)
One of the characteristics that distinguish Islamic Commercial Banks from conventional banks is the existence of a sharia supervisory board (SSB) in an independent Islamic bank and is located parallel to the board of commissioners. SSB has an important and strategic role in implementing sharia in Islamic Banks. SSB is responsible for ensuring all Islamic Bank products and procedures comply with sharia principles. This research is entirely library research. The purpose of this research is to find out how the role of SSB in Islamic banking is related. The analytical method used is the content analysis method. The results of this study indicate that the SSB is an independent body consisting of muamalah sharia experts who also have knowledge in the banking sector at Islamic financial institutions and are in charge of overseeing the implementation of the decisions of the national sharia board at these Islamic financial institutions. SSB has an important and strategic role in implementing sharia principles in Islamic banking. SSB is responsible for ensuring all Islamic bank products and procedures are in accordance with sharia principles.